Distribution of the through-thickness effective stress intensity factor range and its influence on fatigue crack growth rate curves. (June 2022) - Calvín, Giovanna; Escalero, Mikel; Zabala, Haritz; Muñiz-Calvente, Miguel
Abstract: This paper focuses on an analysis of the through-thickness distribution of the effective stress intensity factor range of compact tension specimens, aiming to improve the characterisation of fatigue crack growth rate propagation curves. The maximum stress intensity factor and opening load are evaluated by standard analytical methods and three-dimensional numerical models for various crack lengths and crack front shapes to assess the relevance of considering real crack shapes. The findings reveal that standard procedures attributes only one value of velocity and one value of the fracture parameter for the entire front, whereas numerical methods report different values for both parameters along the thickness. Three-dimensional response surfaces are modelled and validated to estimate the fracture parameters, showing an incongruity in the use of fatigue crack growth rate curves obtained by standard two-dimensional procedures to assess the 3D crack growth. Highlights: An incongruity in the use of fatigue crack growth rate curves obtained experimentally is detected. New analytical equations for obtaining 3D fracture parameters are proposed. Combining an analytical and numerical approach could lead to relevant misestimates of crack growth predictions.